1995
DOI: 10.1207/s15327752jpa6401_5
|View full text |Cite
|
Sign up to set email alerts
|

Assessing Persons With Human Immunodeficiency Virus (HIV) Infection Using the Beck Depression Inventory: Disease Processes and Other Potential Confounds

Abstract: Symptoms of Human Immunodeficiency Virus (HIV) infection and somatic symptoms of depression overlap, confounding clinical assessments of persons with HIV infection. This research examined the extent of this confounding. In Study 1, 71 persons with HIV infection demonstrated high rates of depression on the Beck Depression Inventory (BDI). However, depression scores correlated with symptoms of HIV infection. In Study 2, 63 persons with HIV infection also demonstrated high rates of depression on the BDI, and depr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
60
0
1

Year Published

2005
2005
2022
2022

Publication Types

Select...
7
3

Relationship

0
10

Authors

Journals

citations
Cited by 108 publications
(63 citation statements)
references
References 24 publications
2
60
0
1
Order By: Relevance
“…According to Svanborg and Aberg 4 the BDI is the most often used self-rating instrument for depressive symptoms and when compared with a self-rating version of the Montgomery Asberg Depression Rating Scale (MADRS-S), was found to be equivalent. Similar findings were found by Kalichman et al 5 and Cockram et al 6 when comparing with other rating scales.…”
Section: Inventory (Bdi)supporting
confidence: 90%
“…According to Svanborg and Aberg 4 the BDI is the most often used self-rating instrument for depressive symptoms and when compared with a self-rating version of the Montgomery Asberg Depression Rating Scale (MADRS-S), was found to be equivalent. Similar findings were found by Kalichman et al 5 and Cockram et al 6 when comparing with other rating scales.…”
Section: Inventory (Bdi)supporting
confidence: 90%
“…Scores ranging from 14 to19 and 20 to 28 indicate mild and moderate levels of depressive symptoms, respectively. The Cronbach's alpha for the BDI-II was .92 in a study using 500 psychiatric outpatients (Kalichman et al, 1995). In this study, the Cronbach's alpha for the BDI-II was .91, and the Cronbach's alphas for the cognitive, affective, and somatic subscales were .85, .74, and .83, respectively.…”
Section: Instrumentsmentioning
confidence: 45%
“…Individuals who scored above the standard cut-off of 1.75 were classified as having depressive symptoms. Evidence suggests that the somatic measures in depression diagnostics may inflate depression scores among persons with HIV infection (Kalichman et al 1995), and it has, therefore, been suggested that such somatic measures be removed to prevent the overestimation of depressive symptoms among this population (Kalichman et al 2000). Hence, in this study we included only the affective measures of the DSHSCL when calculating the score and categorizing those as having or not having depressive symptoms.…”
Section: Methodsmentioning
confidence: 99%